PENGARUH KEMAMPUAN MANAJERIAL PIMPINAN TERHADAP MUTU LAYANAN ADMINISTRASI DI PASCASARJANA UIN ALAUDDIN MAKASSAR - Aburizal Akbar; Arifuddin Siraj; Muhammad Yaumi (Fitrah, 2020)
This research article examines the significance of the influence of leadership managerial abilities on the quality of administrative services at the Alauddin State Islamic University in Makassar, while the objectives of this research article are: first, to analyze the reality of the managerial abilities of the postgraduate leadership of Alauddin State Islamic University Makassar; second, analyzing the reality of the administrative service quality of the Postgraduate Administration at the State Islamic University alauddin Makassar; third, to analyze the significance of the influence of the managerial ability of postgraduate leadership on the quality of administrative services at the Alauddin State Islamic University in Makassar. The type of research used is survey research through a quantitative approach with the data collection tool used is a questionnaire, while the analysis used is the product moment analysis and correlation analysis. The indications for the results of this study are that: first, the reality of the managerial ability of the postgraduate leadership of Alauddin State Islamic University Makassar is in the good category (71.4%); second, the reality of the quality of administrative services at the Postgraduate Program at Alauddin State Islamic University in Makassar is in the medium category (65.8%); third, the managerial ability of the postgraduate leadership of the Alauddin State Islamic University in Makassar has a significant effect (16.5%) on the quality of administrative services at the Postgraduate Program at the Alauddin State Islamic University in Makassar.